(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: Describe the current status of human resources and activities of community health workers in District 10 and their advantages and disadvantages. Methods: Quantitative and qualitative mixed research was conducted from March to November 2020. The study surveyed all 92 community health workers with a quantitative questionnaire, then conducted in-depth interviews with 09 collaborators and 03 health workers. Results: The majority of community health workers are managing ≥ 100 households (70.6%). 52.1% of them have participated in > 10 years. Most of them join in many support activities at the commune health station, most are information dissemination (98.9%), and activities such as information collection, participating in health campaigns, training (95.7%), and home visits (92.4%). Their advantages are family support, community recognition, financial and material support. Their disadvantages are family barriers, bad experiences when home visits, low wages, and lack of attention from health workers and commune health stations. Conclusion: It is necessary to have policies and regimes to support and motivate community health workers. In addition, medical staff at health station need to care, listen and share their difficulties and support them to complete their work well.